Evaluation of Hepatitis C Virus and Hepatitis B Virus infection in Drug Abusers - Fawad Mahmood, Nazish Babar, Yasir Ali, Khalida Kousar, Salman Ahmed, Zahid Ullah Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pakistan is one of the world’s uppermost burdens of hepatitis C and B. Our research will assist to enhance and update preventative and treatment methods across the country. Methods: We screened 408 drug abusers for HBV and HCV in the medical and public health literature from study 1 June 2021 to 31 December 2021 on oral and injection drug users from Khyber Pakhtunkhwa Mardan District, Pakistan to evaluate the frequency of hepatitis B and C. Results: Out of 408 half of the individuals were screened for HCV-specific antibodies 204 and 204 for HBV surface antigen by a one-step rapid immune-chromatographic test. For all those who were screened for HCV antibodies, 171 individuals were negative and 30 individuals were positive and 14 % prevalence was observed in drug-addicted individuals. All those were screened for HBV surface antigen 161 individuals were negative and 43 % individuals were positive and 21 % prevalence was observed in drug addicted individuals. According to Age –wise distribution the high prevalence was found between 17-30 years Age 57 % and then followed by the 31-45 years age group having 28 % and the lowest HBV infection was observed in above 45 years Age group was only 15 %. Among HBV 43 positive individuals 70 % were drug abusers while the rest 30 % were oral drug users. In HCV 30 positive individuals 76 % were drug abusers while the rest 23 % were oral drug users. Among drug abusers, an injection drug user infectivity rate of 72 % was high as compared to oral drug abusers' 28 %. Conclusions: Our findings show that the prevalence of HCV and HBV is much higher among IDUs than in the overall population of Pakistan. Injecting drug users are at high risk of HBV and HCV infection transmission, and they can transfer diseases to the community through risky behavior such as syringe exchange and unsafe sex. As a result, various levels of prophylaxis are necessary for these fatal illnesses. Keywords: Drug abuser, Hepatitis B virus, Hepatitis C virus, Pakistan.